Pharmaceutical Interventions In Dental Self-Medication: A Review Of Practices, Challenges, And Regulatory Perspectives In Saudi Arabia (The Review of Diabetic Studies, 2024)
Dental self-medication, particularly the use of analgesics, antiseptics, and antibiotics without professional guidance, remains a growing concern in Saudi Arabia. This review synthesizes recent evidence regarding pharmaceutical interventions and the role of community pharmacists in managing patient requests related to oral and dental health. Studies conducted across the Kingdom indicate a high prevalence of non-prescription antibiotic use, reflecting both cultural acceptance of self-care and gaps in enforcement of dispensing laws (Alghadeer et al., 2018; AlRasheed et al., 2016). Although community pharmacists are often the first point of contact for patients seeking relief from dental pain, research shows inconsistencies in their counseling practices and limited training in dental pharmacotherapy (Allam & Amer, 2020; Alomi et al., 2017).National regulatory reforms, including the 2018 Saudi Food and Drug Authority (SFDA) restriction on antibiotic sales, have marked progress toward rational drug use. However, inconsistent implementation and limited public awareness continue to challenge these efforts (Ministry of Health, 2024). The findings underscore the need for structured pharmacist training programs, stronger inspection mechanisms, and public education campaigns to ensure safe self-medication practices. Aligning these initiatives with Saudi Vision 2030 will enhance oral health outcomes and promote a more sustainable, patient-centered healthcare system.